GRAMMAR TRANSLATION METHOD TO ENHANCE STUDENTS’ WRITING SKILL - Muhammad Chairil Imran; Muthmainnah Mursidin; Mujahidah Adawiah (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2023)
This research seeks to find out the following: 1) whether the Grammar Translation Method improves the writing abilities of students. 2) Ascertain the level of student interest in incorporating the Grammar Translation Method into their educational journey. All participants in this study were students enrolled in classes VIII.1 and VIII.3 at SMP Negeri 1 Pallangga. Investigative methods and a quantitative approach were employed by the researchers. The methods of data collection consist of written examinations and surveys. The research incorporated a population of 396 students and utilized samples from two classes: class VIII.1, which served as the experimental class, and class VIII.3, which functioned as the control class; the combined number of students from these two classes was 72. Applying the Grammar Translation Method to writing skills can result in a substantial enhancement of the teaching and learning process, according to the findings of this study. The mean score for the Experiment class on the pre-test was 56.83, whereas the Control class scored 55.28. The post-test averages were 72.86 for the Control class and 76.58 for the Experimental class. Based on the research findings, it can be inferred that the implementation of the Grammar Translation Method enhances students' writing proficiency and fosters their engagement in the learning.